Avaliação dos efeitos do treinamento do exercício físico aeróbico de curta duração em pacientes hospitalizados com DPOC exacerbado - Knaut, Caroline [UNESP] (2015)
Introduction: Acute Exacerbation (AE) is an important cause of impairment of function in chronic obstructive pulmonary disease (COPD) patients. Negatively affects the quality of life, lung function, muscle weakness, the use of health resources and survival. However, physical exercise performed during the exacerbation can improve the quality of life and the physical capacity of the patient. In this context, this study aims to evaluate the influence of aerobic exercise in hospitalized COPD patients with exacerbation (AECOPD). Objective: To evaluate the effects of short duration aerobic exercise in AECOPD on dyspnea score, quality of life and exercise capacity. Patients and Methods: Twenty-two patients were randomized in two groups; the control group received standard medical treatment and the intervention group that performed aerobic exercise training. All patients performed spirometry, nutritional assessment, distance covered on the six-minute walk test (6MWD), quality of life (Saint George Respiratory Questionnaire- SGRQ), anxiety and depression ( The Hospital Anxiety and Depression Scale), BODE index and intensity of dyspnea (Baseline Dyspnea Index and Modified Medical Research Council Score) after 48 hours of hospitalization and after one month of discharge. The exercise program consisted of aerobic training on a treadmill twice a day for 15 minutes until to the discharge. Results: The impact domain and the total score of quality of life showed a higher increase in the intervention group compared to the control group (p<0.001) when compared to the moments. Both groups showed improvement in the activity domain of SGRQ after one month of hospital discharge, but they did not show difference between groups. Furthermore, only the intervention group showed significant improvement in the symptom domain of SGRQ (p<0.001) and baseline dyspnea index (p=0.006) after one month. 6MWD and BODE did not show difference between ...